Reduced-order hybrid interval observer for verified state estimation of an induction machine. (December 2016) - Krebs, Stefan; Schnurr, Christoph; Pfeifer, Martin; Weigold, Jörg; Hohmann, Sören
Abstract: In this paper, a reduced-order hybrid interval observer for the verified state estimation of an induction machine is designed. The main advantage of this approach over existing ones is the provision of guarantees regarding the estimated states. These guarantees are of particular interest in the case of safety critical systems. In contrast to existing approaches for reduced-order interval observers, the developed observer is applicable to linear time-variant systems. So far, only reduced-order interval observers for time-delay systems have been studied extensively (Perruquetti & Richard, 2013 ). The presented approach is based on a hybridization to bound the real system states between lower and upper bounds. One further novelty is the consideration of a time-variant observer gain whose influence on the estimation is bounded by an interval and included into the observer structure. Finally, it is shown by an experiment that this approach provides a real-time capable way to bound the unmeasurable states of an induction machine. Abstract : Highlights: A method for a verified state estimation of induction machine is proposed. Uncertainties are only assumed to be bounded avoiding unknown stochastic properties. The observer encloses the magnetizing current based on a hybridization approach. Simulations and experimental results show a practically useful interval width.